Identificación, selección y puesta en valor de las fiestas religiosas de la parroquia el paraíso de Celén del cantón Saraguro. - Armijos González, Laura María (2012)
Ecuador as evidence of cultural wealth, protects its territory populations possessing a priceless intangible heritage that is embodied in religious festivals annually to create a strong bond between people and their environment, and thus express the feelings of a people seeks to commemorate and preserve their cultural legacy that identifies them collectively, as the holidays are just temporary spaces more conducive to articulate, renew and transfer a multitude of traditions and customs treasured as the most precious of values. No doubt then that the parties act as areas of concentration and interaction between communities of practice and knowledge repositories unique and tourists, thus providing the host populations of tourism increasingly interested in establishing actions to strengthen its festive heritage that defines as a people, because that is their cultural factor that acts as a stimulant for tourists wishing to move and acquire new cultural experiences, however it is necessary to consider that for a successful party is to be objectively enhancement of so that tourists and locals out to be the beneficiaries. Today, precisely because of the enhancement of the parties has contributed to providing customs and traditions the essence and uniqueness that characterized within the parties, so that the enhancement is a useful mechanism to be considered, as its action means, retrieve, and disseminate boost intrinsic value of each locality, and Ecuador provide a diverse cultural and artistic expressions, is well worth applying this action to stimulate the strengthening of their parties. Against the benefits you get with the start value is the reason why you chose this mechanism to apply in the celebrations of the parish's Paradise Celén, whose project includes general objective "to contribute to the development of the parish Paradise of Celén through the identification, selection and value of their religious festivals, "which allowed us to establish specific goals, the first made to" prepare an assessment of the customs and traditions in the religious festivals of the parish's Paradise Celén "the second focused on" Set alternatives that promote the improvement and enhancement of the main religious festivals of the church "and the third target was raised to" Socialize the results and present the proposal to the relevant authorities " Regarding the methodology used in the first specific objective scientific method was used, involving the historical method which was applied to the elderly witness, field research, observation, analytic-synthetic method, descriptive, systematic Foda analysis of results and, for the second objective was considered systematized in the schedules established for that purpose, Foda analysis and the results obtained in the summary tab inventory of tourist attractions of the Ministry of Tourism, the same way was used as a mechanism to support the observation, photographic documentation, and the structured interview aimed at professionals in the field of culture and tourism, authorities and professional staff of the parish of Celen Paradise, the third objective was developed by publicizing the results of the process research to the authorities called the socialization area, providing audiovisual support material to expose the proposed Events Management. The results of assessment are applied systematically publicizing general data in the first instance of the parish, and later delve into the topic of interest that begins with a description of religious events held during various periods of the year in the parish Paradise of Celén subsequently performed Foda analysis identified six festivals and a specific systematization of information from the parties from the beginning to the present day, attaching to the record on the summary tab of interest include aspects that finally allowed an analysis and discussion of the results of selected religious celebrations With regard to the prioritization of results, we selected two festivals that met the parameters needed to be considered within the hierarchy established in the Methodology II Inventory of Tourist Attractions for the National Tourism Resources Management, also having to support the results the application of Foda analysis. It therefore concluded that the parties have selected certainly favorable to interest potential tourists visit, but that effect is limited evidence of their holiday planning, this is because there is no mechanism to regulate the integration and participation of appropriate to help people to better plan the development of party activities appropriate for valuing. It is therefore recommended to the authorities of the Vestry, priostes stewards to support and maintain the traditions and customs of the population evident in the religious celebrations considering to implement this proposal Events Management raised for this purpose.